Purification of Intact Plant Protoplasts by Flotation at 1g - John Graham (The Scientific World Journal)
From a standard plant tissue digest adjusted to a density of 1.07 g/ml, protoplasts can be harvested by flotation through a low density barrier (1.03 g/ml). The delicate nature of these bodies is suited to this flotation strategy which can be carried out at 1g.